Penerapan Metode Single Exponential Untuk Peramalan Volume Penjualan Minuman Kemasan (Studi Kasus: PT Coca Cola Amatil Indonesia Medan) - Rika Safitri (JURIKOM (Jurnal Riset Komputer), 2019)
PT. Coca Cola Amatil Indonesia Medan is one company that is engaged in producing and distributing packaging beverage products to various regions in need. PT. Coca Cola Amatil Indonesia Medan is in desperate need of forecasting drug sales to increase profits and avoid the occurrence of fatigue or lack of bottled beverage supplies. The parameters or alpha used in forecasting the sales volume of packaged drinks are alpha (α) = 0.1, alpha (α) = 0.3, alpha (α) = 0.5, alpha (α) = 0.7, alpha (α) = 0.9. Single Expontial Smoothing makes a comparison in determining the alpha value, by searching for the alpha value in a trial / random manner to find alpha that has the minimum error with a search using the MSE (Mean Square Error) method. Then the forecasting results that have alpha with the least amount of error value that will be chosen as forecasting for the next period. Expontial Smoothing can only predict one period in the future. At the sample testing stage, it was found that the forecasting results of packaging beverage sales volume for 2017 were 11688380, this result was obtained from data from 2013 - 2016. For testing applications POMQM testing software was used.